2021
DOI: 10.16965/ijpr.2021.109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lung boost device on inspiratory muscle strength in abdominal surgery patients

Abstract: Background: Abdominal surgery involves a surgical repair, resection or reconstruction of organs inside the abdominal cavity. This may include surgery on the stomach, gallbladder, small intestine (colon), liver, pancreas, spleen, esophagus and appendix affected by infection, obstruction, cancerous growth or inflammatory bowel disease. Post Pulmonary Complications (PPCs), are defined as pulmonary anomalies taking place in the postoperative period producing clinically notable, identifiable disease or dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…the study concluded that g lung boost device showed significant improvement in inspiratory muscle strength and in 6 minute walk distance. 16…”
Section: Discussionmentioning
confidence: 99%
“…the study concluded that g lung boost device showed significant improvement in inspiratory muscle strength and in 6 minute walk distance. 16…”
Section: Discussionmentioning
confidence: 99%
“…As a result, additional benefits may include increased walking distance, decreased dyspnoea, enhanced quality of life, and an overall sense of well-being. Lung boost is intended for people with pleural effusion as well as anyone who wants to increase their own power of respiratory muscles and endurance [ 7 ]. Around the world, malignant pleural effusion (MPE) is a common condition with high morbidity and fatality rates.…”
Section: Introductionmentioning
confidence: 99%